Constraints on the Near-Distance Saturation of Ground-Motion Amplitudes for Small-to-Moderate Induced Earthquakes - Atkinson, Gail M.; Yenier, Emrah; Sharma, Nitin; Convertito, Vincenzo (My University, 2016)
The accurate modeling of ground motion for induced-seismicity hazard estimation is critically dependent on how amplitudes scale with distance near the hypocenter. A rich database of ground motions from small events recorded at close distances in the Geysers region of California has been used to constrain the near-distance saturation effects that control the maximum observed ground motions and intensities for shallow-induced events. The results of this study support the modeling of these effects using an equivalent point-source concept, in which the effective source depth increases from a value near 1 km at moment magnitude (M) of 2 to a value near 3 km at M 4. This near-distance saturation behavior can be applied to the development of ground-motion models for induced seismicity in any region.
Keywords: Earthquake; Seismicity hazard; Ground motion